Use of information and communication technologies by the farmers in receiving agricultural information - Alam, Mohammad Zamshed; Uddin, Md Ramiz (Research in Agriculture Livestock and Fisheries, 2018)
The purposes of the study were to determine the extent of use of Information and Communication Technologies (ICTs) by the farmers in receiving agricultural information in Homnaupazilla under comilla district and to explore the contribution of selected characteristics of respondents with their ICTs use in receiving agricultural information. The study was conducted in two villages namely Rampur & Madhabpur of Ghagutia union in Homnaupazilla of comilla district. Data were collected from 110 farmers by using a pre-tested interview schedule during the period from 15 January to 15 March, 2015. Appropriate scales were developed to measure the variables of the study. Descriptive statistics, multiple regression (B) tests were used for analysis. The findings revealed that highest proportion (64.5%) of the respondents’ had medium use of ICTs in receiving agricultural information compared to 13.6 % and 21.8 % having low and high use of ICTs in receiving agricultural information respectively. Education, farm size, annual family income, problem confronted in ICTs use and cosmopoliteness had significant contribution to use of ICTs and provided 51.5 percent contribution to use of ICTs in receiving agricultural information. Findings helps to conclude that educated farmer having large farm size, high annual family income and cosmopoliteness who confronts less problems use more ICTs in their farming practices. All farmers should be encouraged to use ICTs therefore, the Department of Agricultural Extension should focus on personal characteristics of the farmer when motivate them to use more ICTs for getting agricultural information’s for better farming outcome. Res. Agric., Livest. Fish.5(1): 27-32, April 2018